The Representation of Ideology in Academic Textbooks on Iranian History - Zohair Siamian; Maryam Taherzade (تاریخ نگری و تاریخ نگاری)
This study was conducted as part of Vandyke's critical discourse analysis. The texts of academic textbooks on the history of Iran in the Middle Ages, written by native and non-native authors, were examined quantitatively, qualitatively and comparatively in terms of the influence of the authors' ideology, with the aim of providing a methodological model in the analysis of historiographical works in order to determine how the authors' ideology in each text using the linguistic structure, in the narration of single historical events, It leads to making events or people appear more prominent or smaller. According to van's definition, ideologies are the systems of fundamental beliefs of a group and its members that deal with the system of ideas, especially their social, political, or religious ideas. The authors' ideology is also seen in the authors' interpretive schemas of the past and the phrases that show it in the historical narrative, so the rhetoric and speech action in the theory of discourse analysis can be used in the analysis of these texts. Therefore, using the approach and method of van's discourse analysis, it can be claimed that a historical narrative is not a transparent representation or an apocryphal in accordance with the objective reality of a chain of past events, but a single event can be represented and narrated in different narratives in different ways under the influence of the ideology and belief system of the authors.